Interleukin (IL)-6 Inhibits IL-27- and IL-30-Mediated Inflammatory Responses in Human Monocytes - Petes, Carlene; Mariani, Mélissa K.; Yang, Yawen; Grandvaux, Nathalie; Gee, Katrina (Frontiers in Immunology, 2018)
IL-30, the IL-27p28 subunit of the heterodimeric cytokine IL-27, acts as an antagonist of IL-27 and IL-6 signaling in murine cells via gp130 receptor and additional binding partners. Thus far, functions of IL-30 have not been fully elucidated in human cells. We demonstrate that like IL-27, IL-30 upregulated TLR4 expression to enhance LPS-induced TNF-α production in human monocytes; however, these IL-30-mediated activities did not reach the same levels of cytokine induction compared to IL-27. Interestingly, IL-30- and IL-27-mediated IP-10 production required WSX-1 engagement and STAT3 phosphorylation; furthermore, IL-30 induced STAT phosphorylation after 16 hours, whereas IL-27 induced STAT phosphorylation within 30 minutes. This prompted us to examine if a secondary mediator was required for IL-30-induced proinflammatory functions, thus we examined IL-6-related molecules. Combined with inhibition of sIL-6Rα and data showing that IL-6 inhibited IL-30/IL-27-induced IP-10 expression, we demonstrate a role for sIL-6Rα and gp130 in IL-30-mediated activity in human cells.